Optimizing Primary School Students’ Numeracy through Mind Mapping as a Cognitive Organizational Tool - Abdul Majid; Jonathan S Pasinggi; Ahmadi Abd Wahab (International Journal of Educational Development and Innovation, 2026)
This study aims to investigate how the implementation of mind mapping as a cognitive organizational tool can optimize numeracy skills among primary school students. Despite the critical role of numeracy in foundational mathematics, many students struggle to achieve meaningful understanding. This research addresses the need for innovative instructional strategies that enhance conceptual comprehension and retention in elementary mathematics education. A quasi-experimental design was employed with 120 fourth-grade students at SD Negeri 38 Bonto Perak, Pangkep, Indonesia, conducted from October to December 2025. Participants were divided into experimental and control groups. The experimental group received instruction using mind mapping integrated with cognitive organizational strategies, while the control group followed conventional teaching methods. Data were collected using pre- and post-tests measuring numeracy skills, along with classroom observations and student interviews to assess engagement and conceptual understanding. Statistical analysis included paired t-tests and effect size calculations to determine the impact of the intervention. The results indicate that students in the experimental group demonstrated a significant improvement in numeracy skills compared to the control group (mean gain = 18.7 points, p < 0.01). Additionally, students reported higher levels of learning meaningfulness and engagement when using mind mapping as a cognitive organizational tool. The findings suggest that integrating mind mapping into mathematics instruction can enhance numeracy and meaningful learning. However, the study is limited to a specific grade level, school, and region, which may affect generalizability. Future research could explore long-term effects and application across different subjects and educational contexts